A new approach for nano-structuring of glassy selenium (g-Se) using silver nanoparticles (AgNPs) as precursor. (March 2021) - Kumar, Amit; Mehta, N.; Dahshan, A.
Highlights: Synthesis of novel nanocomposite by using glassy Se and Ag nano-particles. Doping of Ag:NPs and alloying of normal Ag powder have been compared. Ag:NPs play important role in nano-structuring of glassy Selenium. Doping of Ag:NPs is found more effective over alloying of normal Ag powder. Abstract: Various routes have been proposed for the synthesis of chalcogen based nanostructured materials but the search of conventional and cost-effective method for the nanostructuring of chalcogenides is an ongoing research activity. This unique work reports the synthesis and the characterization of a novel kind of glassy nanocomposite material belonging to the nano-structuring of g-Se with the help of silver nanoparticles. The local structure is analyzed with the help of X-ray diffraction, Scanning electron microscopy, Raman spectroscopy, and Differential Scanning Calorimetry. It was found that the addition of AgNPs in glassy Se creates fine nano-wires of trigonal Selenium (t-Se) in the glass matrix of g-Se. The electrical, mechanical, and thermal characterizations of the present glassy nanocomposite material have been done in terms of current-voltage characteristics, d.c. conductivity, micro-hardness, and kinetic parameters of glass/crystal phase transformation. A comparative analysis of present glassy composites with a conventional Ag containing glassy alloy (g-Se98 Ag2 ) has also been done to understand the role of incorporation of silver nanoparticles over the normal silver powder. The detailed analysis shows that different physical properties [e.g., thermal stability, modulus of elasticity, micro-hardness, the threshold voltage (i.e., turn-on voltage for resistive switching), and d.c. conductivity] are enhanced more effectively when the nano-structuring of g-Se by using AgNPs is executed as compared to the routine way of alloying.